FACTORS RELATED TO BREASTMILK PRODUCTION ON POSTPARTUM MOTHERS IN EAST PONTIANAK, WEST KALIMANTAN - Otik Widyastutik; YUWAN CHARTASIM; ELLY TRISNAWATI; SELVIANA SELVIANA (The Indonesian Journal of Public Health, 2021)
ABSTRACTProducing breastmilk is a mother’s ability for the next six weeks after giving birth. Based on data from the Health Office of Pontianak City, exclusive breastfeeding coverage is 25% in East Pontianak District. A preliminary study conducted in East Pontianak Sub district, seven out of ten respondents who underwent breastfeeding, their breastmilk was not running well. There are 70% of babies experienced weight increment below 500 grams/month. In addition, 70% mothers drinking less than twelve glasses/day, 70% mothers do not receive support from their husbands in breastfeeding process, 60% mothers have never been exposed to breastfeeding information, and 50% mothers experienced moderate anxiety levels after giving birth. The research aimed to determine the determinants of postpartum mother's milk production in East Pontianak District. This research is observational research with a cross-sectional approach, and the research subject is 48 postpartum mothers. The results showed that the determinant factor could be seen from the relationship of fluid intake (p-value = 0.000), husband's support (p-value=0.000), information exposure (p-value=0.010), supplement (p-value=0.000), and energy intake (p-value=0.000), to breast milk production. Recommendations addressed to the community health center such as work more active in providing counselling, activating cadres by providing practices. Therefore, they can assist in providing knowledge about breastfeeding and making creative promotional media.Keywords : breast milk production, postpartum, nutrition intake